2020
DOI: 10.4103/jets.jets_155_19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided serratus anterior plane block for rib fracture-associated pain management in emergency department

Abstract: Context: Traumatic Rib fractures are common and painful conditions to present in the emergency department. Ultrasound-guided serratus anterior plane block (SAPB) is a newer technique which is being used for managing postthoracotomy, thoracoscopic surgery, or post mastectomy pain by the anesthetists. However, we have recently started utilizing this novel technique in our emergency department for rib fracture patients with severe pain. Settings and Methods: We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The outcomes of the SAPB may differ depending on the type, volume, concentration, and target point of the local anesthetic. In superficial or deep SAPB applications, 10-30 mL of 0.125%-0.375% ropivacaine or bupivacaine were administered and it was reported to provide adequate analgesia for rib fractures, VATS, thoracotomy, breast surgery [ 2 , 12 , 13 ]. In order to avoid the development of a winged scapula and local anesthetic systemic toxicity, we administered 20 mL of 0.25% bupivacaine by USG guidance to apply a deep SAPB.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the SAPB may differ depending on the type, volume, concentration, and target point of the local anesthetic. In superficial or deep SAPB applications, 10-30 mL of 0.125%-0.375% ropivacaine or bupivacaine were administered and it was reported to provide adequate analgesia for rib fractures, VATS, thoracotomy, breast surgery [ 2 , 12 , 13 ]. In order to avoid the development of a winged scapula and local anesthetic systemic toxicity, we administered 20 mL of 0.25% bupivacaine by USG guidance to apply a deep SAPB.…”
Section: Discussionmentioning
confidence: 99%
“…They are a good component of multimodal analgesia, and catheters may be beneficial for patients with an expected duration of moderatetosevere pain of more than twelve hours (54). They can be performed not only by the anaesthetic team but also by emergency department doctors, respiratory and intensive care physicians in different clinical settings (55)(56)(57)(58). It improves patients' access to adequate pain relief and reduces waiting times until the anaesthetist is available to perform the block.…”
Section: Interfascial Chest Wall Blocksmentioning
confidence: 99%
“…With the proliferation of point-of-care ultrasound-guided procedures in the ED, the serratus anterior plane block (SAPB) has been proposed as a readily accessible adjunct analgesic modality. [7][8][9] At present, published evidence for the efficacy of SAPB in the ED setting performed by emergency physicians is mainly limited to case series. [9][10][11] Although a recent study showed improvements in pain and incentive spirometry volumes (ISVs) among patients in the ED after receiving the SAPB, these effects were not compared with a non-intervention group.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] At present, published evidence for the efficacy of SAPB in the ED setting performed by emergency physicians is mainly limited to case series. [9][10][11] Although a recent study showed improvements in pain and incentive spirometry volumes (ISVs) among patients in the ED after receiving the SAPB, these effects were not compared with a non-intervention group. 12 A recent randomized controlled trial of SAPB for rib fractures demonstrated improved pain scores relative to control; however, the blocks were administered by trained anesthesiologists.…”
Section: Introductionmentioning
confidence: 99%